Les effets de l’accompagnement technopédagogique des enseignants sur leurs options pédagogiques, leurs pratiques et leur développement professionnel - Marcel Lebrun; Christelle Lison; Christophe Batier (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Today, we hear more and more about accompaniment of teachers in particular with help of digital and information and communications technology (ICT). But this accompaniment is it effective? What are the most relevant forms of accompaniment? To address this sensitive and difficult issue, we have developed a set of tools to gauge the effects of technopedagogical accompaniment of teachers in higher education. In practical terms, it is (1) instrumentalize some models of staff development of teachers “ICT universe”, (2) to provide tools to measure the effects of different forms of technopedagogical accompaniment, (3) analyze the results of these measurements in three different contexts (Louvain-la-Neuve, Sherbrooke and Lyon) and (4) to compare these results by giving them meaning with respect to preferred methods of accompaniment in these institutions.